Polyurethane-titania composite shell phase change microcapsules and methods of making the same

CN122974227APending Publication Date: 2026-10-27XI'AN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228565.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

(1)传统密胺树脂微胶囊以甲醛、三聚氰胺为单体,制备与长期使用过程中会持续释放游离甲醛,存在人体健康危害与环境污染问题;普通单一聚氨酯壳体仅采用二元醇或二元胺单一单体合成,分子链交联程度低、壳体脆性大,高温下芯材受热膨胀、外力挤压时极易发生囊壁破裂,造成芯材泄漏,且壳体孔隙较多,长期恒温工况下芯材会缓慢渗透,热稳定性与致密性不足

Benefits of technology

(1)聚醚胺与木糖醇复配协同构建聚氨酯交联囊壁,二者分工配合实现壳体柔性与结构强度同步提升:聚醚胺分子链内含可自由旋转的柔性醚键,在聚氨酯骨架中引入软链段,赋予壳体优良韧性,缓冲高温芯材膨胀、外部挤压带来的应力,从根源避免囊壁脆性开裂;木糖醇带有五个多向分布羟基,可与异氰酸酯发生多点交联,在分子层面搭建致密三维网状结构,大幅提高囊壁交联密度、机械强度与耐高温能力。单一使用聚醚胺会导致壳体交联不足、耐热性差,单独采用木糖醇则壳体刚性过强、易碎裂,二者协同反应形成兼具柔性交联网络,完美平衡壳体韧性与结构稳定性,显著降低芯材渗漏风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974227A_ABST
    Figure CN122974227A_ABST
Patent Text Reader

Abstract

The application discloses a polyurethane-titanium dioxide composite shell phase change microcapsule and a preparation method of the microcapsule, and comprises the following steps: preparing a tetrabutyl titanate hydrolysate; preparing an oil phase by using isophorone diisocyanate and a core material, preparing an aqueous phase, and mixing the oil phase and the aqueous phase to obtain a phase change material emulsion; adding polyether amine into the phase change material emulsion and reacting for 2 hours, and then adding xylitol and continuing to react for 2 hours; adding the tetrabutyl titanate hydrolysate into the above reaction system and reacting at 60 DEG C for 2 hours to obtain the composite shell phase change microcapsule. The microcapsule has excellent flexibility and three-dimensional crosslinked structure, the mechanical strength and thermal stability of the shell are greatly improved, and the brittle damage of the capsule wall under high temperature and pressure working conditions can be effectively inhibited; meanwhile, the titanium dioxide hybrid phase filling the shell micro-pores is grown in situ, the shell compactness is further improved, the heat conduction performance of the microcapsule is significantly improved, and the material is endowed with excellent ultraviolet blocking, light-heat conversion and ultraviolet triggered self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of phase change microcapsule material preparation technology, and relates to a polyurethane-titanium dioxide composite shell phase change microcapsule. This invention also relates to a method for preparing the composite shell phase change microcapsule. Background Technology

[0002] Phase change materials (PCAs) absorb and release heat through a solid-liquid phase change process, resulting in high heat storage density and broad application value in fields such as solar thermal energy storage, building temperature control, and thermal management of electronic devices. However, pure PCAs have high fluidity after melting, making them prone to leakage, oxidation, and short service life when used directly. The industry generally adopts microencapsulation technology to encapsulate the PCA core material inside a polymer shell, isolating the core material from the external environment while using the shell to transfer heat and stably perform its heat storage function.

[0003] Currently, the mainstream phase change microcapsule shells are divided into two main categories: organic resin shells and organic-inorganic composite shells. However, existing technologies still have several key drawbacks: (1) Traditional melamine resin microcapsules use formaldehyde and melamine as monomers. During preparation and long-term use, free formaldehyde will be continuously released, which poses health hazards and environmental pollution problems. Ordinary single polyurethane shells are synthesized using only diol or diamine as a single monomer. The degree of cross-linking of molecular chains is low and the shell is brittle. Under high temperature, the core material is easily ruptured when it is heated and squeezed by external force, resulting in core material leakage. In addition, the shell has many pores, and the core material will slowly permeate under long-term constant temperature conditions, resulting in insufficient thermal stability and density.

[0004] (2) Although existing flexible polyurethane shells can reduce the risk of brittle fracture, the cross-linking network is imperfect, and the improvement in heat resistance and mechanical strength is limited; simple cross-linked rigid shells lack molecular chain flexibility and cannot adapt to temperature cycling fluctuations and pressure conditions. Existing technologies cannot balance shell flexibility, cross-linking density and high-temperature stability, and the risk of leakage is prominent in long-term thermal storage applications.

[0005] (3) Pure organic polymer shells have low thermal conductivity, high heat transfer resistance, and limited phase change heat absorption and release rates; at the same time, they only have a single heat storage function, lack photothermal conversion and anti-ultraviolet aging characteristics, and cannot match the solar thermal utilization scenarios. The core material is prone to oxidation and deterioration when exposed to ultraviolet radiation for a long time, and conventional organic shells do not have ultraviolet protection capabilities; microcapsules without inorganic functional phase doping cannot build efficient heat conduction pathways, and additional functions such as photothermal response and self-repair are lacking, which seriously limits the application scenarios.

[0006] Existing research has attempted to modify polyurethane shells by introducing inorganic fillers, but most methods employ physical blending. Inorganic particles tend to agglomerate and have weak bonding with the organic interface, making it difficult to uniformly fill the micropores of the shell, thus limiting the modification and improvement effect. Furthermore, the compatibility between the titanium-source sol-gel in-situ composite process and the polyurethane interfacial polymerization system, as well as the synergistic enhancement mechanism between the organic and inorganic phases, still require further refinement. Therefore, developing an organic-inorganic composite shell phase change microcapsule with high flexibility, high cross-linking density, high thermal conductivity, photothermal conversion, and UV resistance is a crucial technical challenge that urgently needs to be addressed in the field of phase change thermal storage materials. Summary of the Invention

[0007] The purpose of this invention is to provide a polyurethane-titanium dioxide composite shell phase change microcapsule. This microcapsule combines excellent flexibility with a three-dimensional cross-linked network structure, significantly improving the shell's mechanical strength and thermal stability. It can effectively suppress brittle fracture of the capsule wall under high temperature and pressure conditions, and reduce the leakage rate of the phase change core material during long-term use. At the same time, by filling the micropores of the shell with in-situ grown titanium dioxide hybrid phase, the shell's density is further improved, significantly enhancing the overall thermal conductivity of the microcapsule. It also endows the material with excellent UV blocking, photothermal conversion, and UV-triggered self-healing properties, broadening the application scope of phase change microcapsules in solar thermal storage and long-term temperature control.

[0008] The technical solution adopted in this invention is a method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules, which is specifically implemented according to the following steps: Step 1: Prepare a tetrabutyl titanate hydrolysate solution using tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water; Step 2: Prepare an oil phase using isophorone diisocyanate and core material, prepare an aqueous phase using emulsifier and distilled water, and mix the oil phase and aqueous phase to obtain a phase change material emulsion; Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol and continue the reaction for 2 hours. Step 4: Add the tetrabutyl titanate hydrolysate to the reaction system of step 3 and react at 60°C for 2 hours to obtain composite shell phase change microcapsules.

[0009] The invention is further characterized by: Step 1 is as follows: At room temperature, tetrabutyl titanate, anhydrous ethanol, and acetic acid are mixed and stirred. During stirring, deionized water is slowly added dropwise. After the deionized water is completely added, stirring is continued until the aqueous solution turns light blue, thus obtaining a tetrabutyl titanate hydrolysate solution.

[0010] The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0011] Step 2 is as follows: Isophorone diisocyanate and core material are mixed evenly at 35℃~45℃ to form an oil phase. Emulsifier and distilled water are mixed evenly to form an aqueous phase. The oil phase is added to the aqueous phase and emulsified continuously at 40℃ at a speed of 5000~12000 rpm for 15 minutes to obtain a phase change material emulsion.

[0012] The core material is butyl stearate or n-octadecane, and the emulsifier is sodium salt of styrene-maleic anhydride copolymer.

[0013] The mass ratio of isophorone diisocyanate to core material is 0.1~0.3:1, and the mass ratio of emulsifier to core material is 0.04~0.1:1.

[0014] In step 3, the average molecular weight of the polyetheramine is 400, the molar ratio of isophorone diisocyanate to polyetheramine is 2~3:1, and the molar ratio of isophorone diisocyanate to xylitol is 2~4:1.

[0015] In step 4, the mass ratio of tetrabutyl titanate hydrolysate to core material is 0.1~0.3:1.

[0016] Another technical solution adopted in this invention is a polyurethane-titanium dioxide composite shell phase change microcapsule, which is prepared by the above method.

[0017] The beneficial effects of this invention are: (1) Polyetheramine and xylitol are combined to synergistically construct a polyurethane cross-linked capsule wall. The two work together to simultaneously improve the shell's flexibility and structural strength: The polyetheramine molecular chain contains freely rotating flexible ether bonds, introducing soft segments into the polyurethane skeleton, giving the shell excellent toughness, buffering the stress caused by the expansion of the high-temperature core material and external extrusion, and preventing the capsule wall from brittle cracking at the source; Xylitol has five multi-directionally distributed hydroxyl groups, which can cross-link with isocyanate at multiple points, building a dense three-dimensional network structure at the molecular level, which greatly improves the cross-linking density, mechanical strength and high-temperature resistance of the capsule wall. Using polyetheramine alone will result in insufficient shell cross-linking and poor heat resistance, while using xylitol alone will result in an overly rigid shell that is easily broken. The synergistic reaction of the two forms a flexible cross-linked network, perfectly balancing the shell's toughness and structural stability, and significantly reducing the risk of core material leakage.

[0018] (2) Tetrabutyl titanate generates titanium dioxide in situ within the polyurethane shell via sol-gel, forming an organic-inorganic hybrid composite shell. Titanium dioxide particles fill the micropores of the polyurethane shell, further enhancing the shell's density and thermal stability, and providing long-term protection against core material permeation; inorganic titanium dioxide builds continuous thermally conductive pathways within the capsule wall, significantly improving the overall thermal conductivity of the phase change microcapsule and accelerating the heat storage / release response rate.

[0019] (3) The titanium dioxide in the composite shell has ultraviolet absorption characteristics. On the one hand, it can block ultraviolet light and prevent the oxidation and degradation of the internal phase change core material, thus improving the outdoor service life of the material. On the other hand, it gives the microcapsule excellent photothermal conversion capability, which is suitable for solar photothermal storage scenarios. At the same time, it can achieve the self-repair function of ultraviolet-triggered coating cracks by relying on the local photothermal heating effect of titanium dioxide.

[0020] (4) The overall preparation process relies on the integration of interfacial polymerization and sol-gel in-situ composite. The process has good compatibility and is easy to operate. No formaldehyde monomers are used throughout the process, and there is no release of free formaldehyde, making it green and environmentally friendly. The resulting microcapsules are spherical and have a uniform particle size distribution. They have the advantages of multiple functions including heat storage, mechanics, and photothermal properties, and are suitable for various scenarios such as building temperature control, electronic heat dissipation, and solar energy storage. Attached Figure Description

[0021] Figure 1 This is a scanning electron microscope (SEM) image of the phase change microcapsules prepared in Example 1 of this invention. Detailed Implementation

[0022] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0023] The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules of the present invention is carried out according to the following steps: Step 1: Preparation of tetrabutyl titanate hydrolysate At room temperature, tetrabutyl titanate, anhydrous ethanol, and acetic acid were mixed and stirred. While stirring, deionized water was weighed and slowly added to the mixture. After the deionized water was completely added, stirring continued until the aqueous solution turned light blue, thus obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water was 1:2:1.2:4.

[0024] Step 2: Mix isophorone diisocyanate and core material components uniformly at 35℃~45℃ to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer emulsifier uniformly with distilled water to form an aqueous phase; add the oil phase to the aqueous phase, and emulsify continuously at 40℃ for 15 minutes at a speed of 5000~12000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0025] The core material is a low-melting-point fatty acid ester or paraffin hydrocarbon compound, preferably one of butyl stearate or n-octadecane; the mass ratio of isophorone diisocyanate to the core material is 0.1~0.3:1; the mass ratio of emulsifier to the core material is 0.04~0.1:1.

[0026] Step 3: Add polyetheramine to the phase change material emulsion obtained in step 2, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0027] Among them, the polyetheramine is preferably a product with an average molecular weight of 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2~3:1; the molar ratio of isophorone diisocyanate to xylitol is 2~4:1.

[0028] Step 4: Add the tetrabutyl titanate hydrolysate obtained in Step 1 to the reaction system in Step 3, and continue the reaction at 60°C for 2 hours to end the reaction and obtain composite shell phase change microcapsules.

[0029] The mass ratio of tetrabutyl titanate hydrolysate to core material is 0.1~0.3:1.

[0030] Example 1 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0031] Step 2: Mix isophorone diisocyanate and butyl stearate uniformly at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water uniformly to form an aqueous phase; add the oil phase to the aqueous phase, and emulsify continuously at 40°C for 15 minutes at a speed of 5000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0032] The mass ratio of isophorone diisocyanate to butyl stearate is 0.1:1, and the mass ratio of sodium styrene-maleic anhydride copolymer to butyl stearate is 0.06:1.

[0033] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0034] The average molecular weight of the polyetheramine is 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2.6:1; and the molar ratio of isophorone diisocyanate to xylitol is 2.5:1.

[0035] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to butyl stearate is 0.1:1.

[0036] like Figure 1The image shown is an SEM image of the composite shell phase change microcapsules prepared in this embodiment. As can be seen from the image, the prepared microcapsules are spherically distributed, with a complete and dense shell and an average particle size of 8-18 micrometers.

[0037] Example 2 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0038] Step 2: Mix isophorone diisocyanate and n-octadecane at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water to form an aqueous phase; add the oil phase to the aqueous phase and emulsify continuously at 40°C for 15 minutes at 10,000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0039] The mass ratio of isophorone diisocyanate to n-octadecane is 0.2:1, and the mass ratio of sodium styrene-maleic anhydride copolymer to n-octadecane is 0.04:1.

[0040] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0041] The average molecular weight of the polyetheramine is 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2:1; and the molar ratio of isophorone diisocyanate to xylitol is 4:1.

[0042] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours. Then, terminate the reaction to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to n-octadecane is 0.2:1.

[0043] Example 3 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0044] Step 2: Mix isophorone diisocyanate and butyl stearate uniformly at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water uniformly to form an aqueous phase; add the oil phase to the aqueous phase, and emulsify continuously at 40°C for 15 minutes at a speed of 12000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0045] The mass ratio of isophorone diisocyanate to butyl stearate is 0.3:1, and the mass ratio of sodium styrene-maleic anhydride copolymer to butyl stearate is 0.08:1.

[0046] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0047] The average molecular weight of the polyetheramine is 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2.8:1; and the molar ratio of isophorone diisocyanate to xylitol is 3.5:1.

[0048] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours. The reaction is then terminated to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to butyl stearate is 0.3:1.

[0049] Example 4 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0050] Step 2: Mix isophorone diisocyanate and butyl stearate uniformly at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water uniformly to form an aqueous phase; add the oil phase to the aqueous phase, and emulsify continuously at 40°C for 15 minutes at 8000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0051] The mass ratio of isophorone diisocyanate to butyl stearate is 0.25:1, and the mass ratio of sodium styrene-maleic anhydride copolymer to butyl stearate is 0.07:1.

[0052] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0053] The average molecular weight of the polyetheramine is 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2.6:1; and the molar ratio of isophorone diisocyanate to xylitol is 3.5:1.

[0054] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours. Then, terminate the reaction to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to butyl stearate is 0.2:1.

[0055] Example 5 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0056] Step 2: Mix isophorone diisocyanate and n-octadecane at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water to form an aqueous phase; add the oil phase to the aqueous phase and emulsify continuously at 40°C for 15 minutes at 12,000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0057] The mass ratio of isophorone diisocyanate to n-octadecane is 0.1:1, and the mass ratio of sodium salt of styrene-maleic anhydride copolymer to n-octadecane is 0.06:1.

[0058] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0059] The polyetheramine has an average molecular weight of 400; the molar ratio of isophorone diisocyanate to polyetheramine is 3:1; and the molar ratio of isophorone diisocyanate to xylitol is 2.5:1.

[0060] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours. Then, terminate the reaction to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to n-octadecane is 0.25:1.

[0061] Example 6 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0062] Step 2: Mix isophorone diisocyanate and n-octadecane at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water to form an aqueous phase; add the oil phase to the aqueous phase and emulsify continuously at 7000 rpm for 15 minutes at 40°C on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0063] The mass ratio of isophorone diisocyanate to n-octadecane is 0.18:1, and the mass ratio of sodium salt of styrene-maleic anhydride copolymer to n-octadecane is 0.1:1.

[0064] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0065] The average molecular weight of the polyetheramine is 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2.4:1; and the molar ratio of isophorone diisocyanate to xylitol is 2:1.

[0066] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours. Then, terminate the reaction to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to n-octadecane is 0.16:1.

[0067] Example 7 The preparation method of the polyurethane-titanium dioxide composite shell phase change microcapsules in this embodiment is carried out according to the following steps: Step 1: At room temperature, mix tetrabutyl titanate, anhydrous ethanol, and acetic acid while stirring. While stirring, slowly add deionized water to the mixture. After the deionized water is completely added, continue stirring for 10-15 minutes until the aqueous solution turns light blue, obtaining a tetrabutyl titanate hydrolysate solution. The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:4.

[0068] Step 2: Mix isophorone diisocyanate and butyl stearate uniformly at 40°C to form an oil phase; mix sodium salt of styrene-maleic anhydride copolymer with distilled water uniformly to form an aqueous phase; add the oil phase to the aqueous phase, and emulsify continuously at 40°C for 15 minutes at 8000 rpm on a high-speed shear emulsifier to obtain a phase change material emulsion.

[0069] The mass ratio of isophorone diisocyanate to butyl stearate is 0.15:1, and the mass ratio of sodium styrene-maleic anhydride copolymer to butyl stearate is 0.06:1.

[0070] Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol to the reaction system and continue the reaction for 2 hours.

[0071] The average molecular weight of the polyetheramine is 400; the molar ratio of isophorone diisocyanate to polyetheramine is 2.5:1; and the molar ratio of isophorone diisocyanate to xylitol is 3:1.

[0072] Step 4: Add the tetrabutyl titanate hydrolysate to the above reaction system and continue the reaction at 60°C for 2 hours to obtain composite shell phase change microcapsules. The mass ratio of the tetrabutyl titanate hydrolysate to butyl stearate is 0.1:1.

Claims

1. A method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules, characterized in that, The specific steps are as follows: Step 1: Prepare a tetrabutyl titanate hydrolysate solution using tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water; Step 2: Prepare an oil phase using isophorone diisocyanate and core material, prepare an aqueous phase using emulsifier and distilled water, and mix the oil phase and aqueous phase to obtain a phase change material emulsion; Step 3: Add polyetheramine to the phase change material emulsion, heat to 60°C and react for 2 hours, then add xylitol and continue the reaction for 2 hours. Step 4: Add the tetrabutyl titanate hydrolysate to the reaction system of step 3 and react at 60°C for 2 hours to obtain composite shell phase change microcapsules.

2. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1, characterized in that, Step 1 is as follows: At room temperature, tetrabutyl titanate, anhydrous ethanol, and acetic acid are mixed and stirred. During stirring, deionized water is slowly added dropwise. After the deionized water is completely added, stirring is continued until the aqueous solution turns light blue, thus obtaining a tetrabutyl titanate hydrolysate solution.

3. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1 or 2, characterized in that, The mass ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid, and deionized water is 1:2:1.2:

4.

4. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1, characterized in that, Step 2 is as follows: Isophorone diisocyanate and core material are mixed evenly at 35℃~45℃ to form an oil phase. Emulsifier and distilled water are mixed evenly to form an aqueous phase. The oil phase is added to the aqueous phase and emulsified continuously at 40℃ at a speed of 5000~12000 rpm for 15 minutes to obtain a phase change material emulsion.

5. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1 or 4, characterized in that, The core material is butyl stearate or n-octadecane, and the emulsifier is sodium salt of styrene-maleic anhydride copolymer.

6. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1 or 4, characterized in that, The mass ratio of isophorone diisocyanate to core material is 0.1~0.3:1, and the mass ratio of emulsifier to core material is 0.04~0.1:

1.

7. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1, characterized in that, In step 3, the average molecular weight of the polyetheramine is 400, the molar ratio of isophorone diisocyanate to polyetheramine is 2~3:1, and the molar ratio of isophorone diisocyanate to xylitol is 2~4:

1.

8. The method for preparing polyurethane-titanium dioxide composite shell phase change microcapsules according to claim 1, characterized in that, In step 4, the mass ratio of the tetrabutyl titanate hydrolysate to the core material is 0.1~0.3:

1.

9. A polyurethane-titanium dioxide composite shell phase change microcapsule, characterized in that, It is prepared by the method described in any one of claims 1-8.